Anti-aging effect of low molecular weight recombinant humanized collagen on photo-aging by activating adherence junction signaling pathways - Kan Tao; Huilin Zhu; Jing Wei (PLoS ONE, 2025)
Skin aging is characterized by a loss of collagen. Collagen stimulates the secretion of extracellular matrix (ECM) components by skin fibroblasts, contributing to anti-wrinkle and skin-firming effects in cosmetic applications. However, the skin barrier poses a significant challenge to collagen absorption, hindering its dermal functionality. Rapid advancements in synthetic biology have enabled the development of recombinant human collagen (RHC) with controllable sequence and molecular weight, enhancing its potential cosmetic applications. Nonetheless, research on the ability of RHC to penetrate the skin and exert anti-aging effects remains limited, and its underlying mechanisms are largely unexplored. To address this gap, we selected low molecular weight recombinant human collagen peptide (LRHC) and evaluated its skin permeability and anti-aging mechanisms. Findings indicated that LRHC significantly promoted fibroblast proliferation and enhanced the transcription of collagen types I and type III. Furthermore, in photoaged nude mouse models, LRHC upregulated the expression of key basement membrane components, including collagen type IV (COL4), collagen type VII (COL7), collagen type XVII (COL17), integrin β4 (ITGB4), and laminin-332 (LN332, formerly LN5), resulting in increased collagen fiber density. Notably, LRHC demonstrated a dermal permeability rate of 74.7 ± 14.2% after 8 hours. Transcriptome sequencing revealed that LRHC may maintain cytoskeletal structure through activation of adherens junction signaling pathways and promote extracellular matrix (ECM) production through activation of transforming growth factor-beta (TGF-β) signaling pathways, thereby achieving anti-aging efficacy.. These findings confirm that LRHC can penetrate the dermis and exert anti-aging effects on skin, potentially through mechanisms mediated by adherens junction signaling pathways. As a functional active ingredient with anti-aging properties, LRHC holds significant potential for cosmetic applications.